THE INFLUENCE OF MOUNTING STIFFNESS ON THE NATURAL FREQUENCIES OF TWO-DEGREE-OF-FREEDOM SYSTEMS - Made Ayu Sinta Dewi, Ni
The prevention of resonance and the reduction of force transmissibility could be achieved by decreasing the natural frequencies of a system through the addition of elastic material as mounting. Mounting modification is commonly done by means of finite element modelling. Without any reference to the influence of mounting stiffness on the natural frequency of a system, the mounting stiffness is selected by trial and error. Thus, the mounting modification process requires significant time. Because of that, this research aims to study and derive a nondimensional equation that reveals the relationship between the natural frequency of a system and the mounting stiffness, especially for a one-degree-offreedom system and a two-degree-of-freedom system. This research began by modelling machinery as a one-degree-of-freedom system and a two-degree-of-freedom system. It continued by deriving a nondimensional equation that relates mounting stiffness to the natural frequency of each model. Numerical simulation by using several different systems in MATLAB was carried out to verify both equations. At last, the trends of natural frequency decrement due to mounting stiffness reduction from both models were compared to obtain a conclusion. Nondimensional equations that provide the relationship between natural frequency and mounting stiffness for one-degree-of-freedom system and two-degree-of-freedom system have been obtained. These equations reveal that the addition of elastic material as mounting decreases the natural frequency of a system. Furthermore, a guide for choosing between these models has been obtained. The difference between the first and second natural frequency decrement caused by the mounting addition has also been shown.